Pemberdayaan Masyarakat Di Desa Wisata Cikasungka Keramat Solear Kecamatan Cisoka Kabupaten Tangerang ( Makam Keramat Solear ) - Asri Setiani; Desti Nuraeni Nurul Fatya; Siti Intan; Tengku Joevan (LPPM Universitas Pramita Indonesia, 2022)
The research aims to describe 1) the implementation of community empowerment in the Cikasungka Village of Solear Sacred Tourism. 2) The form of community empowerment in the Cikasungka Solear Sacred Tourism Village. (3) Supporting and Inhibiting Factors in the Cikasungka Solear Tourism Village. This research is a qualitative research. The subjects of this study were the Cikasungka Village Government, Solear District, Tourism Awareness Group, and the Cikasungka Keramat Solear Village community. Data collection techniques were carried out through interviews, observation and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of the study revealed that 1) Community empowerment in Cikasungka Wisata Keramat Solear Village was carried out through three stages, namely the awareness stage, the ability transformation stage and the intellectual ability improvement stage. 2) The form of community empowerment through the development of Tourism Villages has involved many surrounding communities in improving community skills and independence, including tourism awareness counseling and Tourism Village Management training. 3) Supporting factors include the potentials that can be developed into the tourism sector to advance the village economy. The enthusiasm and positive response from the community and other inhibiting factors are the quality of human resources which is still low and not yet professional. Inadequate facilities and facilities. There is no record book regarding how many tourists come, how much income you get every day, . Keywords: Community empowerment, development, tourist village